Analisis Faktor Yang Memengaruhi Produktivitas Tenaga Kerja Dan Dampaknya Terhadap Kemiskinan Di Indonesia - Bakir Ahsan; Arroyyan Dylan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
The development of a potential sector cannot be separated from the relationship between stakeholders and economic actors in the region. Because, in essence, the development of potential sectors is carried out by village communities who work together with policy makers at both the village and district levels to provide guidance, direction, coaching and supervision to the community so that they can help in efforts to raise the community's standard of living (Fatmawati et al., 2020).